Epitope-Specific Humoral Responses to Human Cytomegalovirus Glycoprotein-B Vaccine With MF59: Anti-AD2 Levels Correlate With Protection From Viremia - Baraniak, Ilona; Kropff, Barbara; Mclean, Gary R.; Pichon, Sylvie; Piras-Douce, Fabienne; Milne, Richard S. B.; Smith, Colette; Mach, Michael; Griffiths, Paul D.; Reeves, Matthew B. (Journal of Infectious Diseases, 2018)
The human cytomegalovirus (HCMV) virion envelope protein glycoprotein B (gB) is essential for viral entry and represents a major target for humoral responses following infection. Previously, a phase 2 placebo-controlled clinical trial conducted in solid organ transplant candidates demonstrated that vaccination with gB plus MF59 adjuvant significantly increased gB enzyme-linked immunosorbent assay (ELISA) antibody levels whose titer correlated directly with protection against posttransplant viremia. The aim of the current study was to investigate in more detail this protective humoral response in vaccinated seropositive transplant recipients. We focused on 4 key antigenic domains (AD) of gB (AD1, AD2, AD4, and AD5), measuring antibody levels in patient sera and correlating these with posttransplant HCMV viremia. Vaccination of seropositive patients significantly boosted preexisting antibody levels against the immunodominant region AD1 as well as against AD2, AD4, and AD5. A decreased incidence of viremia correlated with higher antibody levels against AD2 but not with antibody levels against the other 3 ADs. Overall, these data support the hypothesis that antibodies against AD2 are a major component of the immune protection of seropositives seen following vaccination with gB/MF59 vaccine and identify a correlate of protective immunity in allograft patients.
EVALuna2:35273